Paglipas ng dilim Cultural Center of the Philippines. - Palma, Precioso; Ignacio, Leon.; Cultural Center of the Philippines ([Pasay City Cultural Promotions Division, Cultural Resources Department, CCP], 1992)
Tanghalang Pilipino's 1991 production of Paglipas ng Dilim. A sarswela or comedy play about values written by Precioso Palma in 1920 and music by Leon Ignacio.
Tape 1 (Songs). Pambungad: Sinasabi nilang ako'y Koplet 1 ni Don Torcuato ; Lakdaw ; Awit ni Caridad/Lakdaw ; Koplet 2 ni Don Torcuato ; Koncertante/finale 1 ; Pambukas ng ikalawang yugto: anong sarap ; Estrella ; Aray ; Awit ni Caridad ; Artista X ; Koplet ni Martin l Aria ni Caridad/finale 2 ; Pambukas ng ikatlong yugto: ang dalaga'y nalulungkot (awit ni Maring) ; Chu, chu, chu ; Oh, pag-ibig ; Kundiman ; At sa dambana/finale 3 ; Pangwakas -- Tape 2. Minus one.
Musical director and conductor, Josefino Toledo ; producers, Della G. Besa, Melissa Corazon Mantaring ; project coordinator, Rommuel Abanto ; recording engineer, Miguel Angelo Silverio.
Recording cast, Josephine Roces (Estrella), Johanna Cabili (Caridad), Sal'my Neo Malaki (Ricardo), Andrew Fernando (Don Torcuato), Ma. Carmila Lopez (Donya Carmen), Ma. Rachelle Gerodia (Maring), Leodigario del Rosario (Martin), Eduardo Briones (Felipe), Emmanuel Margen, Jr. (Luis), Margarita Gomez (Liling), UP Singing Ambassadors.
Keywords: Instrumental ensembles, Arranged -- Philippines; Instrumental music -- Philippines